Entanglement of cultural diversity and future of work: thematic analysis - Mita Mehta; Abhineet Saxena (Cogent Arts & Humanities)
This study explores insights from corporate leaders regarding cultural diversity in the workplace and its potential complexities for the future of work in the context of India. The research aims to develop strategic approaches to blending cultural diversity, helping organizations optimize diversity with minimal conflict through thematic analysis. Exploring the insights from the corporate leaders, the authors conducted a focus group study. 30 corporate experienced corporate leaders participated and responded. Recognizing that cultural diversity is not confined to a single sector, the study gathers perspectives from leaders across diverse industries and predicts potential outcomes through thematic analysis. Four themes emerged from the focus group (1) dynamic leadership, (2) constant communication, (3) talent management, and (4) strategic initiatives. Organizations must focus on these factors to foster an inclusive workplace and ensure a thriving future work environment. Given the limited research in this domain, this study contributes valuable insights into human resource policy and social and managerial implications.